Knowledge-driven risk of diving-induced paralysis: A case-control study among traditional compressor divers in Selayar Regency, Indonesia - Maharja, Rizky; Maharja, Riadnin; Saputra, Edi; Panggeleng, Andi Mifta Farid; Hermawan, Bambang (Community Research of Epidemiology (CORE), 2025)
Previous studies on diving-related paralysis have largely focused on recreational or industrial diving, leaving a critical gap in understanding the knowledge-based risk factors affecting traditional compressor divers in informal, high-risk work environments. This study addresses that gap by examining the association between safety knowledge and paralysis incidence among traditional compressor divers in Menara Indah Village, Selayar Regency, Indonesia. Using a case-control design, 44 male respondents were purposively selected, consisting of 22 cases (with diving-induced paralysis) and 22 controls (without paralysis). Data were collected through structured questionnaires and interviews and analyzed using Odds Ratio (OR) and Population Attributable Risk (PAR). The results revealed that divers with poor safety knowledge had 5.4 times higher odds of experiencing paralysis than those with adequate knowledge. Furthermore, the PAR value of 66.44% indicates that two-thirds of paralysis cases in this population could potentially be prevented through improved safety education. These findings underscore the importance of culturally appropriate, community-based safety training to mitigate health risks in informal marine labor sectors. This study contributes novel empirical evidence to support the integration of public health education within occupational safety frameworks, particularly in underserved coastal communities where traditional diving practices remain widespread and underregulated.